A novel impedance source fed H-type flying capacitor multilevel inverter - Balamurugam, C. R. (International Journal of Applied Power Engineering (IJAPE), 2021)
Â In this paper, simulation using MATLAB-SIMULINK is performed with bipolar triangular fixed amplitude multi-carrier Phase Disposition (PD) PWM strategy with sine wave, Third Harmonic Injection, 60 degree PWM and stepped wave reference for the chosen impedance Source based H-Type flying capacitor Multilevel Inverter (ISBH-Type FCMLI). The root mean square value of the fundamental component and THD of the output voltage which are the most important performance indices for the chosen inverter topologies are evaluated presented and compared for various references through duty ratios. From the simulation results it is observed that for various references the THD is almost similar but the root mean square value in terms of voltage is more for THI, 60 degree PWM and 60 degree reference with phase disposition strategy. The results are obtained for ma < 1 (under amplitude modulation index), ma=1(normal amplitude modulation index) and ma > 1(over amplitude modulation index).